Heavy Metals Pb, Cd and Cu in Palu Bay Waters - Matius Paundanan; Nelky Suriawanto; Moh. Iqbal (Poltekkes Kemenkes Surabaya, 2025)
The coastal waters of Palu Bay are vulnerable to pollution from various activities of the surrounding population. This study aimed to determine the content of heavy metals Pb, Cd, and Cu in the water and sediment of the coastal waters of Palu Bay. The analysis of heavy metal content (Pb, Cd, and Cu) in water and sediment was conducted using an Atomic Absorption Spectrophotometer (AAS). Based on the research, the results showed that the heavy metal content in the water ranged from undetected to 0.04 mg/L for Pb, undetected for Cd and Cu. The heavy metals content in the sediment ranged from 2.17 to 13.8 mg/kg for Pb, undetected to 0.17 mg/kg for Cd, and 5.02 to 37.67 mg/kg for Cu. The Pb content in the water has significantly exceeded the quality standard as stipulated in the Minister of Environment Decree No. 51 of 2004. The Pb content in the sediment is still within safe limits according to Canadian quality standards. The Cd content in the sediment exceeded the quality standard at station 6, while for the other 9 stations, it was not detected. The Cu content in the sediment at 5 stations (2, 3, 4, 5, and 10) has exceeded the Canadian quality standard of 18.7 mg/kg.